Pembangunan Game Pc Berbasis 3d Dengan Teknologi Xna Dan Wiimote - Ricky, Michael Yoseph; Wijaya, Tunjung Agung (Bina Nusantara University, 2010)
The article explains about building a 3D based computer with XNA game engine and WiiMote technology as the controller or in other words, the input device. XNA is a game engine developed by Microsoft for building 2D or 3D game purposes in Xbox console. This engine licenses are free, but not for commercial purposes. WiiMote is Nintendo Wii’s remote control. The remote can be connected to PC by bluetooth connection.